Antimutagenic Potential of Piper sarmentosum Leaf Extracts: Insights from Culinary Preparation - Sanguankaew, Nichakarn; Li , Beilin; Taya, Sirinya; Wongpoomchai, Rawiwan; Khantamat, Orawan (Biomedical Sciences and Clinical Medicine, 2026)
Objective Piper sarmentosum Roxb., a traditional vegetable in Lanna and Thai cuisine, is valued for its flavor but its health-promoting properties after cooking remain unclear. This study investigated the phytochemical profiles, antioxidant capacity, and mutagenicity of its leaf extracts prepared to mimic typical culinary practices. Methods Three P. sarmentosum extracts were prepared: an ethanolic extract of uncooked leaves (PEE), a hot water extract simulating curry broth (PHWE), and an ethanolic extract of boiled leaf residues representing the cooked leaves in curry (PREE). Their chemical composition, antioxidant activity, and antimutagenic effects were evaluated. Results The extracts showed distinct phytochemical patterns. PEE and PREE were rich in phenolics and flavonoids, yielding strong antioxidant activity in ABTS and FRAP assays. PHWE contained higher levels of condensed tannins, reflecting the extraction of water-soluble compounds. None of the extracts showed mutagenicity in the Salmonella assay. Notably, PEE and PREE displayed significant antimutagenic activity against aflatoxin B1 (AFB1) in Salmonella typhimurium strains TA98 and TA100 with metabolic activation. Conclusions P. sarmentosum leaves retain considerable antioxidant and antimutagenic potential after cooking, highlighting their value as a safe and functional food ingredient with potential health benefits.